Retaining blood donors - Marléne Wiggill (Communicare)
Strong organisation-stakeholder relationships contribute to the former attaining its goals. This is also the case with blood services, such as the South African National Blood Service (SANBS). Blood services are dependent on people donating blood to unknown recipients, without remuneration. This paper reports the approach of the SANBS to relationship management with its donors, as well as the perceptions of blood givers of the quality of this relationship. The SANBS’s relationship management approach and activities are analysed from a qualitative approach, using mixed method research, namely qualitative semi-structured interviews and quantitative questionnaires to answer the research questions. The SANBS’s relationship with blood givers is strong, especially regarding relationship satisfaction as outcome. The blood service staff’s behaviour and communication are the main contributors to donor satisfaction, since they provide education and comfort during the donation process. Twoway communication focusing on enhancing the outcomes of relationships, can therefore assist the SANBS in recruiting and retaining donors.